Control of the taeniosis/cysticercosis complex: Future developments - Flisser, A.; Rodríguez Canul, R.; Willingham, Arve Lee (Elsevier, 2006)
Cysticercosis is due to the establishment of the larval stage of the zoonotic cestode parasite Taenia solium. The infection causes substantial human morbidity and mortality, particularly in several Latin American countries and parts of Africa and Asia, as well as economic losses in pig husbandry due to condemnation of infected pork meat. The life cycle of T. solium includes human beings as definitive hosts and pigs as intermediate hosts. Cysticercosis is acquired by the ingestion of eggs released by human tapeworm carriers, who become infected after ingesting pork meat contaminated with cysticerci. Taenia solium transmission has been associated with poverty, lack of sanitary services and practices of rearing backyard pigs with free access to the areas that villagers use as toilets, as well as cultural behaviour. Nonetheless, due to the recent increase of migration and tourism, industrial countries are also reporting cases of human cysticercosis. There are many epidemiological studies that have been conducted mainly in Latin American countries that have evaluated intervention measures for control of cysticercosis including the development and testing of vaccines. Furthermore, the involvement of international agencies and institutions, such as the World Health Organization, the Food and Agriculture Organization and the International Livestock Research Institute, as well as the commitment of policymakers, scientists and field workers, are key means for the sustainable control and, hopefully, eradication of T. solium infections.